Monitoring Process Barriers and Enablers Towards Universal Health Coverage Within the Sustainable Development Goals: A Systematic Review and Content Analysis - Derakhshani N; Doshmangir L; Ahmadi A; Fakhri A; Sadeghi-Bazargani H; Gordeev VS (Dove Medical Press, 2020)
Naser Derakhshani,1,2 Leila Doshmangir,1,3 Ayat Ahmadi,4 Ali Fakhri,5 Homayoun Sadeghi-Bazargani,6 Vladimir Sergeevich Gordeev7,8 1Department of Health Policy & Management, Tabriz Health Services Management Research Center, School of Management and Medical Informatics, Tabriz University of Medical Sciences, Tabriz, Iran; 2Health Management and Economics Research Center, Iran University of Medical Sciences, Tehran, Iran; 3Social Determinants of Health Research Center, Health Management and Safety Promotion Research Institute, Tabriz University of Medical Sciences, Tabriz, Iran; 4Knowledge Utilization Research Center, Tehran University of Medical Sciences, Tehran, Iran; 5Social Determinants of Health Research Center, Kashan University of Medical Sciences, Kashan, Iran; 6Road Traffic Injury Research Center, Tabriz University of Medical Sciences, Tabriz, Iran; 7The Institute of Population Health Sciences, Queen Mary University of London, London, UK; 8Department of Infectious Disease Epidemiology, London School of Hygiene & Tropical Medicine, London, UKCorrespondence: Leila DoshmangirDepartment of Health Policy & Management, Tabriz Health Services Management Research Center, School of Management and Medical Informatics, Tabriz University of Medical Sciences, Daneshgah St, School of Management and Medical Informatics, Tabriz 5165665811, IranTel +98413335229Email Doshmangirl@tbzmed.ac.irBackground: This study builds on previous successes of using tracer indicators in tracking progress towards Universal Health Coverage (UHC) and complements them by offering a more detailed tool that would allow us to identify potential process barriers and enablers towards such progress.Purpose: This tool was designed accounting for possibly available data in low- and middle-income counties.Methodology: A systematic review of relevant studies was carried out using PubMed, ISI Web of Science, Embase, Scopus, and ProQuest databases with no time restriction. The search was complemented by a scoping review of grey literature, using the World Bank and the World Health Organization (WHO) official reports depositories. Next, an inductive content analysis identified determinants influencing the progress towards UHC and its relevant indicators. The conceptual proximity between indicators and categorized themes was explored through three focus group discussion with 18 experts in UHC. Finally, a comprehensive list of indicators was converted into an assessment tool and refined following three consecutive expert panel discussions and two rounds of email surveys.Results: A total of 416 themes (including indicators and determinants factors) were extracted from 166 eligible articles and documents. Based on conceptual proximity, the number of factors was reduced to 119. These were grouped into eight domains: social infrastructure and social sustainability, financial and economic infrastructures, population health status, service delivery, coverage, stewardship/governance, and global movements. The final assessment tool included 20 identified subcategories and 88 relevant indicators.Conclusion: Identified factors in progress towards UHC are interrelated. The developed tool can be adapted and used in whole or in part in any country. Periodical use of the tool is recommended to understand potential factors that impede or advance progress towards UHC.Keywords: universal health coverage, health system, tool development, assessment tool